POSSIBILITIES OF ADDITIVE TECHNOLOGIES IN THE MEAT INDUSTRY. A REVIEW - Nataliya A. Gorbunova (Теория и практика переработки мяса)
Three-dimensional printing (3D printing) is a rapidly developing market of digital technologies with a huge potential for food production, which gives an opportunity to create new food products with the improved nutritional value and sensory profile, and adapted for a particular consumer. The review presents historical aspects of the development of the additive technologies and their classification, examines advantages and drawbacks of the 3D food printing, discusses key aspects of safety of three-dimensional food printing and probable peculiarities of their labeling, analyzes potential possibilities of using the 3DP technology for meat processing and aspects influencing the possibility of printing and following processing of 3D printed meat products.